Importance of Integrating Local Culture- Based Human Values into Elementary School Curriculum - Dewa Nyoman Wija Astawa; I Made Iwan Indrawan Jendra (EDUTEC : Journal of Education And Technology, 2022)
This study discusses why it is important and how to integrate some human values with the local Balinese Hindu teachings into an elementary school curriculum. The study suggests that when taught properly the values could enable collective awareness in the educational level that may impact the development of the generation quality. This qualitative research was carried out at Sathya Sai Elementary School in Denpasar-Bali, a private school that in addition to adopting some universally essential values also features Balinese Hindu teaching. The data were analyzed after long observation on the teaching learning activities as well as through conducting a FGD (focus group discussion) involving the teachers, headmaster, the foundation, and the representative parents of the students. The study shows that integrating such values could be an effective character education needed by the recent generation.